Extra-Judicial Killings: A Snapshot of Bangladesh's Legal Regime (Journal of Legal Studies, 2025)
This study explores the alarming topic of extrajudicial killings in Bangladesh, pointing out how these crimes violate fundamental human rights and undermine democratic values in the country's criminal justice system. It sheds light on the pervasive impunity and lack of accountability among law enforcement agencies by tracing the historical roots of such killings and examining the current judicial system. It investigates the violations of internationally acknowledged human rights instruments and identifies gaps in existing legislation using a qualitative examination of secondary sources. To emphasize the seriousness of the present scenario, two shocking, sensational incidents are reviewed. Upholding the principles of human rights requires that the guidelines, rules, policies, and legal mechanisms made by the UN be put into practice. By putting these recommendations into reality, Bangladesh can create a society that upholds the rule of law, protects human rights, and ends the heinous practice of extrajudicial killings.